The equation of parabola is
[tex] y= ax^2 + bx +c [/tex]
For point (-1,-9), equation of parabola is
[tex] -9 = a(-1)^2 +b(-1)+c \\ -9 = a -b+c [/tex]
For point (1,7), equation of parabola is
[tex] 7 = a(1)^2 + b(1)+c \\ 7 = a + b +c [/tex]
For point (-6,-14), equation of parabola is
[tex] -14 = a(-6)^2 +b(-6)+c \\ -14 = 36a -6b +c [/tex]
So we have three equations , which are
[tex] a - b + c =-9, \\ a + b + c = 7 \\ 36a -6b+c = -14 [/tex]
Subtracting first two equation will give
[tex] -2b = -16 \\ b=8 [/tex]
Subtracting second and third equation gives
[tex] a+b+c-36a+6b-c = 7+14 \\ -35a +7b = 21 \\ -5a + b =3 [/tex]
Substituting 8 for b, we will get
[tex] -5a + 8 =3 \\ -5a = -5 \\ a =1 [/tex]
back substituting 8 for b and 1 for a, we will get
[tex] 1+8+c = 7 \\ c = -2 [/tex]
So we have
[tex] a=1, b=8 and c=-2 [/tex]
Therefore required equation is
[tex] y= x^2 +8x-2 [/tex]